Skip to content

Commit

Permalink
add another solution and some discussion to quadratic f(g(h(x))) = 0
Browse files Browse the repository at this point in the history
  • Loading branch information
E7-87-83 committed Aug 5, 2024
1 parent 9211d0b commit 2bfdf47
Show file tree
Hide file tree
Showing 2 changed files with 83 additions and 2 deletions.
5 changes: 3 additions & 2 deletions Misc/Practice/Practice.tex
Original file line number Diff line number Diff line change
Expand Up @@ -5,7 +5,7 @@
\usepackage{hyperref}

\title{Exercises}
\author{Cecilia Chan, aoiyamada211, Andy}
\author{Cecilia Chan, aoiyamada211, Andy, CY Fung}

\begin{document}
\maketitle
Expand All @@ -15,5 +15,6 @@
\input{Misc/Practice/q2.cecilia.tex}
\input{Misc/Practice/q3.andy.tex}
\input{Misc/Practice/q4.cecilia.tex}
\input{Misc/Practice/q4.cyfung.tex}

\end{document}
\end{document}
80 changes: 80 additions & 0 deletions Misc/Practice/q4.cyfung.tex
Original file line number Diff line number Diff line change
@@ -0,0 +1,80 @@
\section*{Algebra Problem 4, Solution by CY}
\subsubsection*{Problem}
The problems can be found \href{https://www.math.hkust.edu.hk/~makyli/190_2010Sp/problemBk.pdf}{here} on page 7.

\subsubsection*{Solution}

The quadratic functions can be written as $f(x) = \alpha ((x-A)^2 - B)$, $g(x) = \beta ((x-C)^2 - D)$, $h(x) = \gamma ((x-E)^2 - F)$.

\begin{eqnarray*}
f(g(h(x))) =& f(\quad \beta \gamma^2(((x-E)^2-F-\frac{C}{\gamma})^2 - \frac{D}{\gamma^2}) \quad ) \\
=& \alpha \beta^2 \gamma^4 [ [ ((x-E)^2-F-\frac{C}{\gamma})^2 - \frac{D}{\gamma^2} - \frac{A}{\beta\gamma^2} ]^2 - \frac{B}{\beta^2\gamma^4} ].
\end{eqnarray*}

Consider the case $\alpha = \beta = \gamma = 1$:
\begin{equation*}
f(g(h(x))) = [((x-E)^2 - F - C)^2 - D - A]^2 - B.
\end{equation*}

We can see for appropriate transformation, WLOG we can assume a solution of f(g(h(x))) = 0 targetting quadratic polynomials f(x), g(x), h(x) is a set of quadratic polynomials with leading coefficient one.

\hspace{3em}

Solving the equation $ 0 = [((x-E)^2 - F - C)^2 - D - A]^2 - B $, we got eight roots: $E \pm \sqrt{F+C \pm \sqrt{D+A \pm \sqrt{B}}}$.

Assume the parameters are real and no complex roots are involved.

Since square root must be larger than or equal to 0, we can order the eight roots from smallest to largest:

\begin{eqnarray*}
E - \sqrt{F+C + \sqrt{D+A + \sqrt{B}}} \\
E - \sqrt{F+C + \sqrt{D+A - \sqrt{B}}} \\
E - \sqrt{F+C - \sqrt{D+A - \sqrt{B}}} \\
E - \sqrt{F+C - \sqrt{D+A + \sqrt{B}}} \\
E + \sqrt{F+C - \sqrt{D+A + \sqrt{B}}} \\
E + \sqrt{F+C - \sqrt{D+A - \sqrt{B}}} \\
E + \sqrt{F+C + \sqrt{D+A - \sqrt{B}}} \\
E + \sqrt{F+C + \sqrt{D+A + \sqrt{B}}} \\
\end{eqnarray*}

The roots must be corresponding to 1,2,3,4,5,6,7,8. From the sum and difference of root differing by the sign after $E$, we got $E=4.5$,
$ \sqrt{F+C + \sqrt{D+A + \sqrt{B}}} = 3.5 $ for the first pair, $ \sqrt{F+C - \sqrt{D+A + \sqrt{B}}} = 0.5 $ for the fourth pair. (I)

We get $ \sqrt{F+C + \sqrt{D+A - \sqrt{B}}} = 2.5 $ for the second pair, $ \sqrt{F+C - \sqrt{D+A - \sqrt{B}}} = 1.5 $ for the third pair. (II)

From (I) we get $F+C = (12.25+0.25)/2=6.25$ . From (II) we get $F+C = (6.25+2.25)/2 = 4.25 $, which is impossible.

Therefore it is impossible to find quadratic functions $f,g,h$ satisfying the requirement.

\hspace{3em}

Assume the parameters are complex: we have to pair up 1,2,3,4,5,6,7,8 to the roots and it is only possible to get $E=4.5$ for any consistent pairing. Then we can show $F+C$ is real, then similarly for $D+A$ and $B$.
Since $B = [((x-E)^2 - F - C)^2 - D - A]^2$ and $x, E, F+C, D+A$ are real, $B \ge 0$. Similarly we get $D+A - \sqrt{B} \ge 0$, etc.. So it goes back to the assumption that the parameters are real and no complex roots are involved.
\qed

\hspace{5em}

As a bonus, consider the following question from \href{https://math.stackexchange.com/questions/1724410/composition-of-three-quadratic-functions}{Math Stack Exchange}:

\begin{quote}
Find quadratic functions $f,g,h$ such that $f(g(h(x)))$ has $-6, -5, -4, -2, 1, 3, 4, 5$ as its roots.
\end{quote}

Using the above method, we obtain $E=-\frac{1}{2}$, $B=810$, $D+A=106$, $F+C=16\frac{1}{4}$.

We can take on infinitely many solutions. For example, let $D=100$, $F=16$, we have

\begin{eqnarray*}
h(x) =& (x-3\frac{1}{2})(x+4\frac{1}{2}) \\
g(x) =& (x-10\frac{1}{4})(x+9\frac{3}{4}) \\
f(x) =& (x-96)(x+84).
\end{eqnarray*}

Let $D=196$, $F=2\frac{1}{4}$, we have
\begin{eqnarray*}
h(x) =& (x+2)(x-1) \\
g(x) =& x(x-28) \\
f(x) =& x(x+180),
\end{eqnarray*}

which is the solution given in Stack Exchange.

0 comments on commit 2bfdf47

Please sign in to comment.